Laulības reģistrācijas tiesiskā regulējuma evolūcija Latvijā no 1937. gada līdz mūsdienām un iespējamās inovācijas - Kačkere, Ilze (Latvijas Universitāte, 2010)
Darba autore ir izvēlējusies tēmu „Laulības reģistrācijas tiesiskā regulējuma evolūcija Latvijā no 1937.gada līdz mūsdienām un iespējamās inovācijas”, lai aplūkotu laulības reģistrācijas regulējuma attīstību kopš Civillikuma pieņemšanas 1937.gadā līdz mūsdienām. Un izpētītu institūta šī brīža regulējuma efektivitāti un atbilstību mūsdienu prasībām, kad cilvēku vērtības un iespējas ir ļoti mainīgas. Darba pirmajā nodaļā tiek aplūkota laulības institūta izpratne ģimenes tiesībās kopumā, tā kā šobrīd sabiedrības apziņā bieži vien jēdzieni „laulība” un „ģimene” ir sinonīmi. Kā arī dots neliels ieskats šī institūta regulējumam Latvijā 20.gadsimta sākumā. Darba otrajā nodaļā tiek analizēta laulības reģistrācijas tiesiskā regulējuma attīstība kopš 1937.gada, kas mainās atbilstoši valstī pastāvošajai iekārtai. Atsevišķi tiek nodalīta laulības reģistrācija dzimtsarakstu nodaļās un baznīcās, tā kā uz abām neattiecas vienāds normatīvo aktu regulējums, izņemot Civillikumā noteiktās pamatprasības. Savukārt trešajā nodaļā tiek analizēta šī brīža regulējuma efektivitāte un atbilstība mūsdienu prasībām, kā arī tā nepilnības. Tādēļ darba autore izvirza vairākus priekšlikumus tā uzlabošanai, kā svarīgākos norādot uz nepieciešamību noregulēt garīdznieka tiesisko statusu reģistrējot laulības. Izslēgt no normatīvo aktu regulējuma laulības izsludināšanas institūtu, tā kā tas šobrīd vairs nespēj pildīt savu uzdevumu, un pašas dzimtsarakstu nodaļas un baznīcas varētu veikt personu iesniegumos sniegto ziņu pārbaudi. Kā arī nepieciešamību izvērtēt laulības reģistrēšanas uzdevuma deleģēšanu tikai šobrīd Civillikumā norādītajām konfesijām, ņemot vērā, ka atjaunojot spēkā 1937.gada Civillikumu, netika izvērtēta ne to iespēja nodrošināt likuma prasību izpildi, ne arī vēlme uzņemties šo valsts uzdevumu.

Master thesis is „The evolution of the legal regulation of marriage registration process in Latvia since 1937 and it’s possible innovations”. The goal of the thesis is to consider the development of regulation of the marriage registration since the adoption of the Civil law in 1937 till nowadays, as well as to research the effectiveness of the current regulation provided by the institution of marriage registration and its compliance with contemporary demands of individuals taking into account the variability of human values and possibilities. The first chapter of the thesis deals with the general conception of the marriage institution in family law since nowadays the concepts of “marriage” and “family” are synonyms in the public consciousness. This chapter provides general review of the regulation of the particular institution in Latvia at the beginning of the 20th century, as well. In the second chapter of the thesis the development of legal regulation of the marriage registration has been analyzed since 1937 that is subordinated to changes in the political system. Since the regulation of legislation differs for the registration of marriage at the civil registry office and at the church except for the basic requirements provided by the Civil law, the registration of marriage at the civil registry office has been separated from the registration of marriage at the church. The third chapter focuses on the analysis of the effectiveness of the current regulation and its compliance with the contemporary demands, as well as its disadvantages. All things considered the author of the thesis has proposed possible innovations for the improvement of legal regulation of marriage registration process. One of the main suggestions is the necessity of regulation of the customs status of the clergyman in the process of the regulation of marriage. Another proposal deals with the necessity to exclude the announcing institution of marriage from the regulation of legislation since it is no longer able to ensure its purpose, therefore, the civil registry office and the church could carry out the task of the verification of information given in application by person. Eventually the author of the thesis proposes to evaluate the delegation of the marriage registration only to the denominations currently provided by the Civil law, taking into account the fact that at the time the reenactment of the 1937 Civil law took place the feasibility of the particular denominations to comply with the requirements of legislation, as well as their desire to carry out the task of marriage registration, were not considered.
The evolution of the legal regulation of marriage registration process in Latvia since 1937 and it's possible innovations
Keywords: Juridiskā zinātne